We're no angels [videorecording (DVD)] - Mamet, David; Jordan, Neil, 1950-; De Niro, Robert; Penn, Sean, 1960-; Moore, Demi; Kirby, Bruno, 1949-2006 (Widescreen DVD collection., 2004)
Two escaped convicts' only prayer is to pass themselves off as clergymen. As men of the cloth, they are able to pass right through a police blockade at the border and into the safety of Canada.